A meta‐analysis on morphological, physiological and biochemical responses of plants with PGPR inoculation under drought stress. (27th October 2022) - Zhao, Xiaowen; Yuan, Xiaomai; Xing, Yuanjun; Dao, Jicao; Zhao, Deqiang; Li, Yuze; Li, Weiwei; Wang, Ziting
Abstract: Plant growth‐promoting rhizobacteria (PGPR) can help plants to resist drought stress. However, the mechanisms of how PGPR inoculation affect plant status under drought remain incompletely understood. We performed a meta‐analysis of plant response to PGPR inoculation by compiling data from 57 PGPR‐inoculation studies, including 2, 387 paired observations on morphological, physiological and biochemical parameters under drought and well‐watered conditions. We compare the PGPR effect on plants performances among different groups of controls and treatments. Our results reveal that PGPR enables plants to restore themselves from drought‐stressed to near a well‐watered state, and that C4 plants recover better from drought stress than C3 plants. Furthermore, PGPR is more effective underdrought than well‐watered conditions in increasing plant biomass, enhancing photosynthesis and inhibiting oxidant damage, and the responses of C4 plants to the PGPR effect was stronger than that of C3 plants under drought conditions. Additionally, PGPR belonging to different taxa and PGPR with different functional traits have varying degrees of drought‐resistance effects on plants. These results are important to improve our understanding of the PGPR beneficial effects on enhanced drought‐resistance of plants.